PENINGKATAN KINERJA GURU IPA MELALUI TEKNIK SUPERVISI KUNJUNGAN KELAS DI SMP - Medi Mursalin (UNIVERSITAS BENGKULU, 2016)
The general objective of this research was to improve the performance of science teacher’s performace through the class visit supervision technique in Junior high school 1 TetapKaur regency. The subjects of this research is the science teacher of Junior high school 1 Tetap, Kaur Tegency. This is action research which is conducted in three phases. The techniques of data collecting were interview, obsevation, and quetionare by communicative approach and processmodel. The data analisys tehniques is qualitative decriptive. The result of tthis reasearch is the teacher performance was improved by class visit supervision technique, this mean the better we conduct class visit supervision technique, so the better the performance of science teacher.Keywords: class visit supervision, science teacher’s performance